O literackim debiucie Andrieja Sobola - Hazan, Vladymyr (Studia Rossica Posnaniensia, 2012)
The article examines the early steps in the literature of a prominent Russian writer, Andrey Sobol (1888–1926). The first published story A. Sobol himself pointed to was “Chelovek s prozvischami” (A Man with Nicknames), which appeared in print in 1913. In fact, A. Sobol’s literary debut took place much earlier – in 1904. As the author of the article believes, Sobol attempted to cut out the first texts from his biography because these were unskillfully written. However, it is important to consider his literary debut in order to understand the evolution which Sobol accomplished from his early works to becoming an interesting and brilliant writer.